Cover Picture: Spectroelectrochemical Evaluation of a ZnO Optically Transparent Electrode Prepared by the Spin‐spray Technique (Electroanalysis 8/2020). Issue 8 (7th August 2020) - Okazaki, Takuya; Taniguchi, Hiroaki; Wagata, Hajime; Ito, Mizuki; Kuramitz, Hideki; Watanabe, Tomoaki
Abstract : The cover image is based on the Full Paper Spectroelectrochemical Evaluation of a ZnO Optically Transparent Electrode Prepared by the Spin‐spray Technique by Takuya Okazaki et al., DOI: 10.1002/elan.202000028.